Development and validation of the Mentalizing Emotions Questionnaire: a self-report measure for mentalizing emotions of the self and other - Kasper, Lea A.; Hauschild, Sophie; Berning, Anna; Holl, Julia; Taubner, Svenja (PLOS ONE, 2024)
Mentalizing describes the ability to imagine mental states underlying behavior. Furthermore, mentalizing allows one to identify, reflect on, and make sense of one’s emotional state as well as to communicate one’s emotions to oneself and others. In existing self-report measures, the process of mentalizing emotions in oneself and others was not captured. Therefore, the Mentalizing Emotions Questionnaire (MEQ; current version in German) was developed. In Study 1 (N = 510), we explored the factor structure of the MEQ with an Exploratory Factor Analysis. The factor analysis identified one principal (R2 = .65) and three subfactors: the overall factor was mentalizing emotions, the three subdimensions were self, communicating and other. In Study 2 (N = 509), we tested and confirmed the factor structure of the 16-items MEQ in a Confirmatory Factor Analysis (CFI = .959, RMSEA = .078, SRMR = .04) and evaluated its psychometric properties, which showed excellent internal consistency (α = .92 - .95) and good validity. The MEQ is a valid and reliable instrument which assesses the ability to mentalize emotions provides incremental validity to related constructs such as empathy that goes beyond other mentalization questionnaires.
Gesehen am 04.11.2024